Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/adhm.201500795
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Mesenchymal Stem Cells Allows for Microvascularized Bone Tissue‐Like Environments in PEG Hydrogels

Abstract: In vitro engineered tissues which recapitulate functional and morphological properties of bone marrow and bone tissue will be desirable to study bone regeneration under fully controlled conditions. Among the key players in the initial phase of bone regeneration are mesenchymal stem cells (MSCs) and endothelial cells (ECs) that are in close contact in many tissues. Additionally, the generation of tissue constructs for in vivo transplantations has included the use of ECs since insufficient vascularization is one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…It has previously been shown that MSCs are able to spread, migrate, and build cellular networks in this artificial ECM microenvironment. [ 6a,10 ] Similarly to when cells are grown as 2D monolayers (tissue culture glass, TCG), MSCs in hydrogels deposited extracellular proteins in their vicinity within 24 h, as visualized by l ‐azidohomoalanine (AHA) labeling of nascent protein deposition prior to fixation and without membrane permeabilization (Figure 1c). However, whereas cells in 2D monolayers produce a fibrillar protein network, cells in 3D rather start to deposit a dense matrix shell surrounding themselves.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that MSCs are able to spread, migrate, and build cellular networks in this artificial ECM microenvironment. [ 6a,10 ] Similarly to when cells are grown as 2D monolayers (tissue culture glass, TCG), MSCs in hydrogels deposited extracellular proteins in their vicinity within 24 h, as visualized by l ‐azidohomoalanine (AHA) labeling of nascent protein deposition prior to fixation and without membrane permeabilization (Figure 1c). However, whereas cells in 2D monolayers produce a fibrillar protein network, cells in 3D rather start to deposit a dense matrix shell surrounding themselves.…”
Section: Resultsmentioning
confidence: 99%
“…A methodology that is capable of patterning local environments within a single tissue construct would allow for the optimization of conditions for both tissues, while still benefiting from the interactions between different cell types. Approaches where growth factors are patterned within hydrogels in order to achieve vascularized bone tissue have for instance been investigated . Coupling osteogenic and angiogenic cues in a scaffold can potentially form an early vascular network by encapsulated cells preventing an ischemic environment to sustain cellular viability in nonhealing defects.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) is a hydrophilic polymer of ethylene glycols that, when crosslinked in aqueous solution, forms biocompatible hydrogels . As an example, vascularized bone marrow‐like tissue constructs were formed in a synthetic transglutaminase (FXIII) crosslinked PEG hydrogel which enables cell migration by matrix MMP‐sensitive peptide sequence and cell attachment by peptide arginine‐glycine‐aspartic acid (RGD) domain . The flexibility and capability to control the cell adhesion and cell‐mediated degradation by using this method allow the study of EC behavior in governing vascularization of tissues.…”
Section: Design Consideration: How Simple Is Complex Enough?mentioning
confidence: 99%